Business and System Analysis in Batik Online Platform for Plus Size - Livani, Livani; Eng, Kho I; Purnama, James (Journal of Applied Information, Communication and Technology, 2020)
Batik industry has mostly been producing apparels only for standard size and none of the online platform that sells batik has been supported body positivity campaign. Another problem is found in the online stores, which do not support multi stores. Most of the existed marketplaces do not provide multi store for the users. There exists platform with multi store capability. However, the users have to pay a substantial amount of fee for the activation [magento]. Therefore, the purpose of this research is to analyze the business process of creating an online platform to sell batik specifically to people with oversize condition with multi stores capability. The multi store capability (done by other research fellows) is part of a project, which includes this research. We have conducted preliminary online research and interview and surveys after the prototype has been launched to get feedback from users. Users believe the idea of the platform and the development is a good start and it has contributed to positive .